The whole ten yards - Samaha, Elie, 1955-; Kaufman, Allan; Rifkin, Arnold; Willis-Watkins, David; Gallo, George, 1956-; Deutch, Howard; Willis, Bruce, 1955-; Perry, Matthew, 1969-; Peet, Amanda, 1972-; Pollak, Kevin, 1958-; Henstridge, Natasha; Collison, Frank, 1950-; et al. (Burbank, CA : Warner Home Video, 2004)
Former hitman Jimmy "The Tulip" Tudeski has retired and is living a quite life of cooking and houskeeping in Mexico. Jimmy has been able to convice the authorities he's dead thanks to falsified dental records by his former neighbor Oz, who now lives in Los Angeles. But appearently not everyone has been fooled when Oz's wife, Cynthia, is kidnapped by Lazlo Gogolak and his goons. Gogolak is a member of the Hungarian mafia, and Jimmy previously murdered his son, so he's abducted Cynthia in order to get Oz to reveal Jimmy's current whereabouts.
Based on the characters created by Mitchell Kapner.
Director of photography, Neil Roach ; editor, Seth Flaum ; music, John Debney ; costume designer, Rudy Dillon ; production designer, Ginny Randolph-Weaver.
Bruce Willis, Matthew Perry, Amanda Peet, Kevin Pollak, Natasha Henstridge, Frank Collison, Johnny Messner, Silas Weir Mitchell.
MPAA rating: PG-13; for sexual content, some violence and language.
DVD, Region 1, full screen (1.33:1) presentation; Dolby Digital 5.1 surround.
English or dubbed French dialogue, French or Spanish subtitles; closed-captioned.
Keywords: Assassins -- Drama; Dentists -- Drama; Kidnapping victims -- Drama; Asesinos -- Teatro; Feature films; Comedy films; Films for the hearing impaired